2020
DOI: 10.1088/1367-2630/abc6e6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning on the electron–boson mechanism in superconductors

Abstract: To unravel pairing mechanism of a superconductor from limited, indirect experimental data is always a difficult task. It is common but sometimes dubious to explain by a theoretical model with some tuning parameters. In this work, we propose that the machine learning might infer pairing mechanism from observables like superconducting gap functions. For superconductivity within the Migdal–Eliashberg theory, we perform supervised learning between superconducting gap functions and electron–boson spectral functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…One of the obstacles to such achievement is the calculation of (EBSF) and to address this, supervised and UML methods were applied. The results showed that the proposed methods could precisely predict EBSF with an accuracy above 99.9% [321]. Much research has been conducted to analyse the static properties of in-gap bound states for single and multiple quantum dots.…”
Section: Ai For Physics Of Scsmentioning
confidence: 93%
“…One of the obstacles to such achievement is the calculation of (EBSF) and to address this, supervised and UML methods were applied. The results showed that the proposed methods could precisely predict EBSF with an accuracy above 99.9% [321]. Much research has been conducted to analyse the static properties of in-gap bound states for single and multiple quantum dots.…”
Section: Ai For Physics Of Scsmentioning
confidence: 93%
“… 25 , 26 , 27 ML models using different algorithms were trained to predict the existence of superconductivity and the T c of superconductors. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 Progress has been made in several areas, such as how T c varies with doping, 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 the descriptors indicating superconducting mechanism, 36 , 37 , 38 , 39 structural factors affecting T c , 43 , 44 and candidates of new high- T c superconductors. 46 , 51 So far, ML models predicting T c have yielded good predictive scores.…”
Section: Introductionmentioning
confidence: 99%